The Influence of Job Security on Employee Welfare Moderated by Organizational Support for Contract Employees of the Padang City Fire Department, Indonesia - Hayatie, Syarifah; Sandi, Hendrik Heri (Manunggal Halim Jaya, 2025)
Employee welfare is one of the important factors in human resource management (HR) and creating a productive work environment. This study aims to analyze the effect of job security on employee welfare with organizational support as a moderator. The research method used is quantitative with a descriptive approach. Data was collected by distributing questionnaires to 140 contract employees and analyzed using Structural Equation Modeling (SEM). The study results indicate that job security has a positive and significant effect on employee welfare, as it is essential to help employees not worry about their future careers, promotions, and safety in the workplace. In addition, organizational support is a moderating variable that strengthens the relationship between job security and employee welfare. This finding proves that the higher the employee's perception of organizational support, the higher the positive influence of job security on well-being, especially for contract employees.